Enhancing the role of nutrition professionals in weight management: A cross‐sectional survey. (29th November 2014) - Bleich, Sara N.; Bandara, Sachini; Bennett, Wendy; Cooper, Lisa A.; Gudzune, Kimberly A.
<x xml:space="preserve">Abstract</x> Objective (1) To determine the nonphysician health profession perceived as best qualified to provide weight management. (2) To examine nutrition professionals' current practice characteristics and perceived challenges and solutions for obesity care. (3) To examine the association between nutrition professionals' quality of training and self‐efficacy in weight management. Methods A 2014 national cross‐sectional online survey of 500 U.S. nonphysician health professionals (100 from each: nutrition, nursing, behavioral/mental health, exercise, pharmacy) was analyzed. Results Nutrition professionals most commonly self‐identified as the most qualified group to help patients lose weight (92%), sentiments supported by other health professionals (57%). The most often cited challenge was lack of patient adherence (87%). Among nutrition professionals, 77% reported receiving high‐quality training in weight loss counseling. Nutrition professionals who reported high‐quality training were significantly more likely to report confidence (95% vs. 48%) and success (74 vs. 50%) in helping obese patients lose weight (P < 0.05) than those reporting lower‐quality training. Conclusions Across all nonphysician health professionals, nutrition professionals were identified as best suited to provide routine weight management counseling to obese patients. Yet nutrition professionals' receipt of high‐quality weight management training appears critical to their success in helping patients lose weight.